The Changing Patterns of Financial Integration in Latin America - Didier, Tatiana; Moretti, Matias; Schmukler, Sergio L. (World Bank Group, Washington, DC, 2015)
This paper describes how Latin America and the Caribbean has been integrating financially with countries in the North and South since the 2000s. The paper shows that the region is increasingly more connected with the rest of the world, even relative to gross domestic product. The region's connections with South countries have been growing faster than with North countries, especially during the second half of the 2000s. Nevertheless, North countries continue to be the region's principal source and receiver of flows. The changes reflect significant increases in portfolio investments, syndicated loans, and mergers and acquisitions. Growth of greenfield investments has been more subdued after the initial high level. Greenfield investments in the region have been in sectors in which the source country has a comparative advantage, not where the receiver country has an advantage. Mergers and acquisitions have been in sectors in which the receiver country has a comparative advantage.